COMMUNITY-BASED ENTREPRENEURSHIP AND MSME RESILIENCE:BUILDING SUSTAINABLE LOCAL ECONOMIC ECOSYSTEMS - Nida Garnida Fitrianti; Raden Roro Fatmasari (Journal of Jabar Economic Society Networking Forum, 2024)
Background: Micro, small, and medium enterprises (MSMEs) are central to local employment, household income, and the circulation of economic value, yet their resilience is frequently constrained by fragmented support, weak market linkages, limited managerial capability, and dependence on individual entrepreneurs. Community-based entrepreneurship offers a complementary perspective by locating enterprise development within social relationships, local institutions, shared resources, and place-based knowledge. Aims: This article develops an integrative conceptual framework explaining how community-based entrepreneurship can strengthen MSME resilience and contribute to sustainable local economic ecosystems. Research Method: The study uses an integrative conceptual review of established literature on community-based enterprise, entrepreneurial ecosystems, social capital, local economic development, and organizational resilience. It does not claim primary survey data, experimental evidence, or statistical estimates. Results and Conclusion: The synthesis indicates that MSME resilience is strengthened when local entrepreneurial activity is supported by trusted networks, collective learning, market access, institutional coordination, resource diversification, and mechanisms that connect individual firms with community capabilities. Community embeddedness can reduce information gaps and transaction frictions, but excessive closure may also restrict innovation and external market access. Sustainable local ecosystems therefore require a balance between strong local ties and outward-facing connections. Contribution: The paper proposes a Community-Based MSME Resilience Framework linking community assets, entrepreneurial coordination, ecosystem resources, adaptive capability, and sustainable local outcomes. It provides propositions and practical indicators for future empirical testing.